PENGARUH RASIO LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN PANDEMI COVID-19 SEBAGAI VARIABEL MODERASI - Putri Budi Aryani, Pande Nyoman; Agung Suaryana, I Gusti Ngurah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.11.TAHUN.2024, 2024)
The value of healthcare sector companies has fluctuated soaring in 2020 due to a positive performance during Covid-19 Pandemic. The purpose of research is to obtain empirical evidence regarding the effect of liquidity ratios and profitability ratios on firm value moderated by the Covid-19 Pandemic. This study uses a population of health sector companies that are listed on the Indonesia Stock Exchange (IDX) until 2021. The sampling method for this study was purposive sampling method. Based on the specified criteria, there were 17 companies during 4 years of observation from 2018-2021, so the final sample was 68 samples. The research data collection method is a non-participant observation method. The data analysis technique of this research is the Moderated Regression Analysis (MRA) test. The results of this study indicate that the liquidity ratio and profitability ratio have a significant positive effect on firm value and the Covid-19 Pandemic moderates the effect of the liquidity ratio and profitability ratio on firm value. The implications of this research are to confirm signal theory and contingency theory, add information to management about the importance of liquidity and profitability during the Covid-19 Pandemic so that company value increases, and assist investors in making decisions.